2016
DOI: 10.1159/000443847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Omega-3 and Vitamins E + C Supplements on the Concentration of Serum B-Vitamins and Plasma Redox Aminothiol Antioxidant Status in Elderly Men after Strength Training for Three Months

Abstract: Background: Data on redox plasma aminothiol status in individuals on strength training are very limited. Therefore, we studied the effect of omega-3 and vitamins E + C supplementation on the concentration of B-vitamins and redox aminothiol status in elderly men after strength training for 3 months. Methods: Healthy men, age 60 ± 6 (mean ± SD) were randomly divided into 3 groups: group I received placebo (n = 17), group II consumed omega-3 (700 mg, n = 17), and group III consumed vitamins E + C (235 mg +1 g, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…While the available information is limited and currently inconclusive, a randomized controlled trial in young healthy subjects showed that daily intake of fish oil (2 g; majorly consisting of DHA and EPA) resulted in a significant decrease of SUA after 4 and 8 weeks of supplementation [27]. A similar significant decline in SUA was also observed in healthy elderly men consuming daily supplement pills characterized by ω-3 FAs such as DHA and EPA for three months, although the change was not extensive [28]. Based on these pieces of evidence, increasing the daily intake of ω-3 FAs via eating pattern changes, such as appropriate choice of aliments and cooking oils, might be beneficial to health in terms of SUA management.…”
Section: Discussionmentioning
confidence: 95%
“…While the available information is limited and currently inconclusive, a randomized controlled trial in young healthy subjects showed that daily intake of fish oil (2 g; majorly consisting of DHA and EPA) resulted in a significant decrease of SUA after 4 and 8 weeks of supplementation [27]. A similar significant decline in SUA was also observed in healthy elderly men consuming daily supplement pills characterized by ω-3 FAs such as DHA and EPA for three months, although the change was not extensive [28]. Based on these pieces of evidence, increasing the daily intake of ω-3 FAs via eating pattern changes, such as appropriate choice of aliments and cooking oils, might be beneficial to health in terms of SUA management.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, PUFA intake was lower in the high uric acid group. Previous studies examining the relationship between fatty acid intake and serum uric acid levels include a randomized controlled trial comparing the effects of fish oil intake containing n-3 PUFA [14], an intervention study using n-3 PUFA supplements [15], and an intervention study using a calorie-restricted diet in which SFA was replaced with unsaturated fatty acids [16]. The difference in the fatty acid intake between the two uric acid level groups observed in this study seems to be consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding dietary style, the Dietary Approaches to Stop Hypertension (DASH) diet and the Mediterranean diet reduce serum uric acid [11][12][13]. However, only a few studies have investigated the relationship between serum uric acid levels and dietary lipids [14][15][16]. An intervention study in healthy young adults revealed that n-3 polyunsaturated fatty acid intake with 2 g/day of fish oil for 8 weeks reduced serum uric acid levels [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro study using URAT1-expressing 293A cells reported that EPA and DHA were strong inhibitors of URAT1 dependent urate transport leading the authors to suggest these fatty acids could have urate lowering potential in humans through their uricosuric effects [ 10 ]. In a small study of 17 health men aged on average 60 years, consumption of 700 mg of omega three fatty acids (260 mg DHA and 260 mg EPA) and strength training for three months resulted in a statistically significant reduction in serum urate; pre median (range) 0.37 (0.27–0.63)mmol/l and post 0.36 (0.24–0.48) mmol/l; p = 0.017 [ 11 ]. In another small study of healthy young people consumption of 2 g fish oil daily (each 1 g capsule containing 490 mg DHA and 98 mg EPA) for eight weeks led to a significant reduction in serum urate; mean (SD) baseline 0.347 (0.025) mmol/l; week four 0.260 (0.017) mmol/l and week eight 0.308 (0.018) mmol/l p < 0.05 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%